TOXIC IMPLICATIONS OF HEAVY METALS IN DRINKING WATER SOURCES OF LOKO AND MARARRABA IN NASARAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Metals are substances with high electrical conductivity, malleability, and luster, which voluntarily lose their electrons to form cations. This study aimed at assessing the Toxic implications of Heavy Metals in Drinking Water Sources of Loko and Mararraba in Nasarawa using Micro Plasma Atomic Emission Spectroscopy (MP-AES). The results showed that, seven heavy metals along with their respective concentrations for both Loko and Mararraba in mg/L (Zn (0.19 and 0.23), Cd (0.00 and 0.00), Fe (0.05 and 0.04), Cu (0.01 and 0.01), Pd (0.01 and 0.01), Ni (0.003 and 0.002) and Mn (0.092 and 0.027)) respectively were present in the water samples. The Hazard Quotient (HQ) was all recorded to be lower than unity. The Hazard Index (HI) was also recorded to be 4.6x10-4 and 5.7 x 10-4 for both Loko and Mararraba respectively, value less than unity. This makes non-carcinogenic effects negligible. The total excess life cancer risk was found to be 36.1.4x10-13 and 41.46x10-13 for both Loko and Mararraba respectively, value less than that of U.S (1.0x10-4 to 1.0x10-6) and South Africa (5.0x10-6). This makes carcinogenic effects negligible. Regular monitoring and evaluation of the water at the sample locations is recommended.
Keywords: Heavy metals; cancer risk; total risk; hazard quotient; hazard index; micro plasma atomic emission spectroscopy.